Combination of Constraint-Induced Movement Therapy with Electroacupuncture Improves Functional Recovery following Neonatal Hypoxic-Ischemic Brain Injury in Rats. (7th February 2018) - Kim, Hyunha; Koo, Young Soo; Shin, Myung Jun; Kim, Soo-Yeon; Shin, Yong Beom; Choi, Byung Tae; Yun, Young Ju; Lee, Seo-Yeon; Shin, Hwa Kyoung
Abstract : Aim . Neonatal hypoxic-ischemia (HI) due to insufficient oxygen supply and blood flow during the prenatal and postnatal periods can cause cerebral palsy, a serious developmental condition. The purpose of this study was to investigate the efficacy of combining constraint-induced movement therapy (CIMT) and electroacupuncture to treat rat neonatal HI brain injury. Methods . The left common carotid arteries of postnatal day 7 rats were ligated to induce HI brain injury, and the neonates were kept in a hypoxia chamber containing 8% oxygen for 2 hrs. Electroacupuncture at Baihui (GV 20) and Zusanli (ST 36) was performed concurrently with CIMT 3 weeks after HI induction for 4 weeks. Results . Motor asymmetry after HI was significantly improved in the CIMT and electroacupuncture combination group, but HI lesion size was not improved. The combination of CIMT and electroacupuncture after HI injury increases NeuN and decreases GFAP levels in the cerebral cortex, suggesting that this combination treatment inversely regulates neurons and astrocytes. In addition, the combination treatment group reduced the level of cleaved caspase-3, a crucial mediator of apoptosis, in the cortex. Conclusions . Our findings indicate that a combination of CIMT and electroacupuncture is an effective method to treat hemiplegia due to neonatal HI brain injury.